Genetic markers of white matter integrity in schizophrenia revealed by parallel ICA - Gupta, Cota Navin; Chen, Jiayu; Liu, Jingyu; Damaraju, Eswar; Wright, Carrie; Perrone-Bizzozero, Nora I.; Pearlson, Godfrey; Luo, Li; Michael, Andrew M.; Turner, Jessica A.; Calhoun, Vince D. (Frontiers in Human Neuroscience, 2015)
It is becoming a consensus that white matter integrity is compromised in schizophrenia (SZ), however the underlying genetics remains elusive. Evidence suggests a polygenic basis of the disorder, which involves various genetic variants with modest individual effect sizes. In this work, we used a multivariate approach, parallel independent component analysis (P-ICA), to explore the genetic underpinnings of white matter abnormalities in SZ. A pre-filtering step was first applied to locate 6527 single nucleotide polymorphisms (SNPs) discriminating patients from controls with a nominal uncorrected p-value of 0.01. These potential susceptibility loci were then investigated for associations with fractional anisotropy (FA) images in a cohort consisting of 73 SZ patients and 87 healthy controls. A significant correlation (r=-0.37, p=1.25×E-6) was identified between one genetic factor and one FA component after controlling for scanning site, age and sex. The identified FA-SNP association remained stable in a 10-fold validation. A 5000-run permutation test yielded a p-value of 2.00×E-4. The FA component reflected decreased white matter integrity in the forceps major for SZ patients. The SNP component was overrepresented in genes whose products are involved in corpus callosum morphology (e.g., CNTNAP2, NPAS3 and NFIB) as well as canonical pathways of synaptic long term depression and protein kinase A signaling. Taken together, our finding delineates a part of genetic architecture underlying SZ-related FA reduction, emphasizing the important role of genetic variants involved in neural development